Inside Front Cover: DHA and EPA Prevent Seizure and Depression‐Like Behavior by Inhibiting Ferroptosis and Neuroinflammation via Different Mode‐of‐Actions in a Pentylenetetrazole‐Induced Kindling Model in Mice. Issue 22 (21st November 2022) - Wang, Xueyan; Xiao, Aiai; Yang, Yueqi; Zhao, Yingcai; Wang, Cheng Cheng; Wang, Yuming; Han, Jun; Wang, Zhengping; Wen, Min
Abstract : Mol. Nutr. Food Res . 2022, 66, 2200275 DOI: 10.1002/mnfr.202200275 Dietary supplementation of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) suppressed iron dyshomeostasis, oxidative stress and neuroinflammation in PTZ‐induced kindling model mice. DHA and EPA are demonstrated to regulate the Nrf2 signaling and inhibit NLRP3 inflammasome activation via different mode‐of‐actions, implying great and different potential in the prevention and treatment of epilepsy. This is reported by Min Wen and co‐workers in article number 2200275 .